Single-copy gene fluorescence in situ hybridization and genome analysis: Acc-2 loci mark evolutionary chromosomal rearrangements in wheat - Danilova, Tatiana V.; Friebe, Bernd R.; Gill, Bikram S. (My University, 2012)
Fluorescent in situ hybridization (FISH) is a useful tool for physical mapping of chromosomes and studying evolutionary chromosome rearrangements. Here we report a robust method for single-copy gene FISH for wheat. FISH probes were developed from cDNA of cytosolic acetyl-CoA carboxylase gene (Acc-2) and mapped on chromosomes of bread wheat, Triticum aestivum L. (2n=6x=42, AABBDD), and related diploid and tetraploid species. Another nine full-length cDNA FISH probes were mapped and used to identify chromosomes of wheat species. The Acc-2 probe was detected on the long arms of each of the homoeologous group-3 chromosomes (3A, 3B, and 3D), on 5DL and 4AL of bread wheat, and on homoeologous and nonhomoeologous chromosomes of other species. In the species tested, FISH detected more Acc-2 gene or pseudogene sites than previously found by PCR and Southern hybridization analysis and showed presence/absence polymorphism of Acc-2 sequences. FISH with the Acc-2 probe revealed the 4A-5A translocation, shared by several related diploid and polyploid species and inherited from an ancestral A-genome species, and the T. timopheevii specific 4A[superscript t]-3A[superscript t] translocation.
Citation: Danilova, T. V., Friebe, B., & Gill, B. S. (2012). Single-copy gene fluorescence in situ hybridization and genome analysis: Acc-2 loci mark evolutionary chromosomal rearrangements in wheat. Retrieved from http://krex.ksu.edu
Keywords: Wheat; Single-copy gene fluorescence in situ hybridization; Acetyl-CoA carboxylase; Karyotype evolution